THE ROLE OF PHYSICAL-QUALITY-DEVELOPING EXERCISES AIMED AT IMPROVING THE TECHNIQUE OF HAMMER THROWERS AT THE STAGE OF LONG-TERM TRAINING - Erkuziyevich, Ruzimatov Islomjon (Research Focus International Scientific Journal, 2026)
This article presents information on the organization of training sessions aimed at developing and improving the technique of throwers in sports schools, as well as on the development of their physical qualities. The article widely uses a complex of special exercises to improve the technique of hammer throwers during training and to develop physical qualities in order to achieve high results in competitions.